2017
DOI: 10.1016/j.ijpddr.2017.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of Schistosoma mansoni in infected mice by slow release of artemisone

Abstract: The current treatment of schistosomiasis is based on the anti-helminthic drug praziquantel (PZQ). PZQ affects only the adult stages of schistosomes. In addition, resistance to PZQ is emerging. We suggest a drug, which could serve as a potential alternative or complement to PZQ, and as a means of treating infections at earlier, pre-granuloma stage. Derivatives of the peroxidic antimalarial drug artemisinin have been indicated as alternatives, because both plasmodia and schistosomes are blood-feeding parasites. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 43 publications
1
15
0
Order By: Relevance
“…Likewise, a single oral dose of artesunate (400 mg/kg in 3% ethanol and 7% Tween 80) given 21 days post-infection, yielded a 66% reduction of worm load [10]. A similar procedure using other artemisinin derivatives (artemiside, artemisone, CKWO3 and artemether) yielded more than 90% reduction [5]. Significant reduction of S. mansoni load was found in infected mice treated with new artemisinin derivatives, artesunic acid and dihydroartemisinin acetate [12].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, a single oral dose of artesunate (400 mg/kg in 3% ethanol and 7% Tween 80) given 21 days post-infection, yielded a 66% reduction of worm load [10]. A similar procedure using other artemisinin derivatives (artemiside, artemisone, CKWO3 and artemether) yielded more than 90% reduction [5]. Significant reduction of S. mansoni load was found in infected mice treated with new artemisinin derivatives, artesunic acid and dihydroartemisinin acetate [12].…”
Section: Discussionmentioning
confidence: 99%
“…Details of upkeep of the life cycle relied on description by Gold et al [84] and performed at Tel Aviv University (Tel Aviv University ethical committee number 01-13-076). Six-week-old male ICR mice were purchased from Harlan Laboratories (Rehovot, Israel) and infected individually by subcutaneous injection with the parasite's cercariae obtained from infected snails which were raised and kept at 26°C in aeriated aquaria.…”
Section: Maintenance Of the Schistosome Life Cyclementioning
confidence: 99%
“…We observed that the anti-mycobacterial activity of both Artemisia-derived natural products was not dependent on an endoperoxide bridge. Artemisinin, artesunate, artemisone, dihydroartemisinin and artemether, all with endoperoxide bridges, have shown to be effective against S. mansoni , through the peroxidative activity [10,11]. However, we found neither deoxyartemisinin nor artemisinic acid exhibited any effect on S. mansoni viability or mobility (data not shown), which could be caused by the lack of endoperoxide bridges in both compounds.…”
Section: Discussionmentioning
confidence: 60%